PENGARUH KEAKTIFAN MENGIKUTI KEGIATAN IPNU IPPNU TERHADAP MOTIVASI BELAJAR PAI SISWA KELAS XI DI SMK ISLAM NUSANTARA KECAMATAN COMAL - Auliya Nisa 'Arofani; Santika Lya Diah Pramesti (Tadrib: Jurnal Pendidikan Agama Islam, 2021)
The purpose of this study is to explain the activity of students participating in IPNU IPPNU activities at SMK Islam Nusantara, Comal District, Pemalang Regency, to describe the motivation to learn PAI for class XI students at SMK Islam Nusantara, Comal District, Pemalang Regency and to determine the effect of active participation in IPNU IPPNU activities on the motivation to learn PAI in class XI students. at SMK Islam Nusantara, Comal District, Pemalang Regency.This type of research is field research using a quantitative approach. The main data sources of this research, which include; member of IPNU IPPNU class XI SMK Islam Nusantara Comal. Methods of data collection using a questionnaire (questionnaire), as well as documentation. While the data analysis method used quantitative data analysis method of simple linear regression statistical analysis.The results of the research are the active participation in IPNU IPPNU activities with an average of 42 located in the 39-46 interval in the good category, the PAI learning motivation has an average of 42 located in the 39-43 interval with the sufficient category. Calculation with a simple linear regression formula, namely = 16.836 + 0.584X. Then obtained the ttest value of 5.418. At a significant level of 5%, the value of ttable = 2,024, then ttest = 5,418 > ttable = 2,024, then Ha is accepted and Ho is rejected, and at a significant level of 1%, the value of ttable = 2,711, then ttest = 5,418 > ttable = 2,711 with Ha accepted and Ho rejected. It was concluded that there was a significant influence between the activity of participating in IPNU IPPNU activities on the motivation to learn PAI for class XI students at SMK Islam Nusantara, Comal District, Pemalang Regency